Multipoint Hydrogen Bonding‐Based Molecular Recognition of Amino Acids and Peptide Derivatives in a Porous Metal‐Macrocycle Framework: Residue‐Specificity, Diastereoselectivity, and Conformational Control. Issue 22 (18th February 2021) - Tashiro, Shohei; Nakata, Kosuke; Hayashi, Ryunosuke; Shionoya, Mitsuhiko
Abstract: Porous crystals have great potential to exert space‐specific functions such as multipoint molecular recognition. In order to rationally enhance the porous function, it is necessary to precisely control molecular recognition event in the pores. Hydrogen bonding is an effective tool for controlling molecular recognition. However, multiple hydrogen bonds, which are essentially the origin of high complementarity and specificity, remain difficult to innovate in porous crystals in an intelligent way. This paper demonstrates molecular recognition of amino acid and peptide derivatives by multipoint hydrogen bonding in a porous metal‐macrocycle framework revealed by single‐crystal X‐ray diffraction analysis. l ‐Serine residues are site‐selectively and residue‐specifically adsorbed on the pore surface via multiple hydrogen bonds. A serine derivative is diastereoselectively recognized on the ( P )‐ or ( M )‐side of the enantiomeric pore surface. Moreover, the conformation of the peptide is highly regulated, incorporating a poly‐l ‐proline type I helix‐like structure into the pore. These findings will bring deep scientific knowledge to the design of new porous crystals and functions. Abstract : Amino acid and peptide derivatives are site‐selectively recognized in a porous metal‐macrocycle framework through multiple hydrogen bonding. Serine residues are diastereoselectively and residue‐specifically adsorbed on the pore‐surface through multiple hydrogen bonds. In addition, conformation of a peptide adsorbed on the pore‐surface is highly controlled to adopt a poly‐l ‐proline type I helix‐like structure.